Climate Crisis : ‘Listening to the Science’ Not Enough - Sofiah Jamil (2020)
Greta Thunberg has called on politicians to “listen to the science” and take climate change seriously. But climate communication strategies can be more effective when “listening to the science” is complemented with “listening to society”.